Analisis Bibliometrik Potensi Antoksidan Lengkuas Merah (Alpinia purpurata): Teknik Ekstraksi dan Aktivitas Penangkapan Radikal Bebas - Dwi Endah Kusumawati; Davia Maulidda Suharno (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Health issues related to free radicals remain a serious concern in Indonesia as they can trigger oxidative stress and degenerative diseases. Red ginger (Alpinia purpurata) is a rhizome plant with potential as a source of natural antioxidants due to its secondary metabolite content; however, its effectiveness is highly influenced by extraction techniques. Although numerous experimental studies have been conducted, a systematic research mapping on this topic is still lacking. This study aims to perform a bibliometric analysis of scientific publications regarding the antioxidant potential of red ginger, focusing on extraction techniques and free radical scavenging activity. The research method employs a quantitative analysis using data sourced from the Scopus database for the 2015–2025 period. Through specific inclusion and exclusion criteria, 38 relevant articles were obtained and analyzed using VOSviewer 1.6.20 software. The results indicate that publication trends have fluctuated, reaching a peak in 2024. Research distribution is dominated by Asian countries, with India, Thailand, and Indonesia as the primary contributors. Network visualization reveals three main clusters focusing on bioactivity, phytochemistry, chemical analysis, antimicrobial activity, and extraction techniques. A research gap was identified for the Alpinia purpurata species compared to Alpinia galanga, as well as opportunities for developing advanced instruments such as LC-MS and other complex analytical techniques. The implications of this study highlight the need for further exploration into 'nanoemulsion' and 'green extraction' to enhance the bioavailability of red ginger's antioxidant compounds in the development of future innovative pharmaceutical products